Peningkatan Kapasitas Aparatur Desa dalam Pembentukan Peraturan Desa (Perdes) Berbasis Bukti (Evidence-Based Policy) di Kabupaten Maros - Muhammad Tang Abdullah; Nurdin Nara; Syahribulan Syahribulan; Amril Amril; Rizal Pauzi; Musran Munize; Wahyu Nurdiansyah (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Law Number 6 of 2014 concerning Villages gives broad authority to villages to regulate and manage the various needs and interests of the community. Village government officials are required to have the capacity to draft regulations in the village. However, the facts show that the capacity of the village government apparatus is still weak in forming regulations in the village, especially the preparation of evidence-based village regulations. This fact also occurred in Maros Regency, especially in Moncongloe District. This phenomenon underlies the importance of conducting training for village apparatus in drafting regulations in the village. This technical guidance was carried out for 8 hours in the Hall of the Moncongloe District Office and was attended by 30 people and facilitated by a team of lecturers from the Faculty of Social and Political Sciences, Hasanuddin University. To find out the effectiveness of this training, a pre-test evaluation was carried out at the beginning and a post-test at the end of the training. The results of the evaluation showed that there was an effect of the training on the participants, namely increasing their knowledge of evidence-based technical regulations in villages.